PERFOMANCE OF INNOVATIVE LEADERSHIP STYLE - Pribadi Widyatmojo; Istiana Rahatmawati (Eksos LPPM, 2015)
Work excellency suppose to be prepaired before it come through. It needs management, andself-improvement. For improving work place relations. For improving relations at home.Environment turbulency forces organization management to prepaire suitable strategy to facethe turbulency. Transformational leadership style is the way to prepaire organization to facethe turbulency, because it is capable of improving member participation, in order to improveorganization innovation, so that organization performance grows up.This research support that telecomunication industry which has organization climate toimprove member participation capable of improving organization member performance inorder to face the turbulence. The reseach finding discussed.Keyword: leadership, improving, environment turbulency